2002
DOI: 10.2337/diabetes.51.8.2522
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Suppresses Glucose-Induced Mitochondrial ATP Production and Insulin Release by Generating Reactive Oxygen Species in Pancreatic Islets

Abstract: We examined the effects of reduced Na ؉ /K ؉ -ATPase activity on mitochondrial ATP production and insulin release from rat islets. Ouabain, an inhibitor of Na ؉ /K ؉ -ATPase, augmented 16.7 mmol/l glucose-induced insulin release in the early period but suppressed it after a delay of 20 -30 min. Unexpectedly, the ATP content in an islet decreases in the presence of 16.7 mmol/l glucose when Na ؉ /K ؉ -ATPase activity is diminished by ouabain, despite the reduced consumption of ATP by the enzyme. Ouabain also sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 52 publications
(46 reference statements)
1
49
0
1
Order By: Relevance
“…In a previous study, we found that ouabain reduces not only the increment in ATP content and the hyperpolarisation of mitochondrial membrane potential by glucose, but also the increment in O 2 consumption by glucose [17]. Since increased O 2 consumption occurs in uncoupling [38], ouabain-induced suppression of mitochondrial ATP production clearly is not mediated by uncoupling, and the suppression may derive from direct or indirect effects on the respiratory chain.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In a previous study, we found that ouabain reduces not only the increment in ATP content and the hyperpolarisation of mitochondrial membrane potential by glucose, but also the increment in O 2 consumption by glucose [17]. Since increased O 2 consumption occurs in uncoupling [38], ouabain-induced suppression of mitochondrial ATP production clearly is not mediated by uncoupling, and the suppression may derive from direct or indirect effects on the respiratory chain.…”
Section: Discussionmentioning
confidence: 90%
“…We have found that ouabain decreases glucose-induced insulin release by reducing ATP content [17]. In addition, high glucose-induced hyperpolarisation of mitochondrial membrane potential was inhibited by ouabain.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…An o ther impo r ta nt po in t which ca n lead to worsening of this condition is that β cells contain low levels of antioxidative enzymes such as CAT, SOD and GPx and thus they can only weakly defend against oxidative stress [10][11][12] . These findings have demonstrated the major destructive role of oxidative stress in islet transplantation and have encouraged investigators to use antioxidants during the isolation phase and the entire transplantation process to overcome the final lack of healthy islets.…”
Section: Islet Isolation and Role Of Oxidative Stressmentioning
confidence: 99%